(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to know and measure the role of interactive marketing in its dimensions (interaction, trust, communication, rapid response, service quality) in achieving the customer experience in its dimensions (sensory component, emotional component, cognitive component, behavioral component, material component), if the research field is represented in the sports sector and the research community is the members of the Sports Clubs Fans Association, which amounted to (114) members, and a sample of (88) members was selected based on the (Thompson) equation and clarifying the relationship between the research variables. A main hypothesis was formulated to test the relationship of correlation and influence. The researcher relied on the descriptive analytical approach in completing the research and analyzing the data. The statistical program (Spss.v.24) and (Amos.v,24) were used. Among the statistical methods used were (arithmetic mean, standard deviation, coefficient of variation, multiple linear regression, structural equation modeling, confirmatory factor analysis, exploratory factor analysis (Cronbach‘ s Aipha). According to the results obtained, the researcher reached several conclusions, the most important of which is that interactive marketing The speed of response, communication and interaction that it includes leads to improving the customer experience and the public’s acceptance of the failures that the club may experience as a result of the lack of trust and transparency between them to clarify the reasons and results. As for the most important recommendations that the researcher emphasized, the club’s management must ensure the speed of response, communication and continuous interaction as they are part of the system of positive experience and the value perceived by the public, and the reasons for failures and failure to provide the service must be clarified.